Undernutrition and obesity among elderly people living in two cities of developing countries: Prevalence and associated factors in the EDAC study. (October 2017) - Jésus, Pierre; Guerchet, Maëlenn; Pilleron, Sophie; Fayemendy, Philippe; Maxime Mouanga, Alain; Mbelesso, Pascal; Preux, Pierre Marie; Desport, Jean Claude
Summary: Background: Nutritional status among elderly people living in Sub-Saharan Africa is poorly studied, even though undernutrition and obesity are known to cause many complications and are risk factors for progression and death in several diseases. The aims of this study were to assess the nutritional status of the elderly in Central Africa and to study the factors associated with nutritional disorders (undernutrition and obesity). Methods: Two cross-sectional population-based studies were carried out in the capitals of Central African Republic (CAR) and Republic of Congo (ROC) between 2008 and 2009. Participants were aged ≥65 years old and underwent nutritional assessment including the following measurements: weight, height, body mass index (BMI), waist circumference (WC). Diet was also investigated. Nutritional status was defined according to the WHO BMI classification (<18.5 = undernutrition; ≥30 = obesity). Multinomial regression analysis was performed in order to identify factors associated with nutritional status. Results: 990 elderly people underwent nutritional assessment (482 in CAR and 508 in ROC). Mean BMI was 22.7 ± 4.8 kg/m 2 . The prevalence of undernutrition was 19.2% and was lower in ROC than in CAR (9.5% vs. 29.5%; p < 0.0001). The prevalence of obesity was 8.8% and was higher in ROC than in CAR (14.6% vs. 2.7%; p < 0.0001). The mean WC was 85.3 ± 28.4 cm. Adjusted on study site, increasing age (OR = 1.6 [95% CI: 1.1–2.3] for 75–84 years, OR = 2.6 [95% CI: 1.4–4.8] for 85+ years), occupation as farmer/breeder (OR = 2.2 [95% CI: 1.1–4.2]), smoking (OR = 1.71 [95% CI: 1.14–2.56]) and low sugar consumption (OR = 1.7 [95% CI: 1.1–2.7]) were positively associated with undernutrition whereas only female sex was positively associated with obesity (OR = 5.0 [95% CI: 2.2–11.0]). Conclusions: The prevalence of undernutrition is high in the elderly population of these countries, in contrast to obesity. Undernutrition and obesity are associated with different socio-economic factors and food consumption. Simple nutritional advice could contribute to improving the nutritional status of elderly people in Central Africa.